The impact of COVID-19 on mentoring early-career investigators: "Everything can wait. Listen more than usual and share your own struggles". Issue 40 (8th October 2021) - Johnson, Mallory O.; Gandhi, Monica; Fuchs, Jonathan D.; Sterling, Lauren; Sauceda, John A.; Saag, Michael S.; Riley, Elise D.; Sevelius, Jae M.
Abstract : Abstract: The COVID-19 pandemic disrupted almost all sectors of academic training and research, but the impact on human immunodeficiency virus (HIV) research mentoring has yet to be documented. We present the perspectives of diverse, experienced mentors in a range of HIV research disciplines on the impact of COVID-19 on mentoring the next generation of HIV researchers. In November to December, 2020, we used an online data collection platform to cross-sectionally query previously-trained HIV mentors on the challenges related to mentoring during the pandemic, surprising/positive aspects of mentoring in that context, and recommendations for other mentors. Data were coded and analyzed following a thematic analysis approach. Respondents (180 of 225 mentors invited [80% response]) reported challenges related to relationship building/maintenance, disruptions in mentees' training and research progress, and mentee and mentor distress, with particular concerns regarding mentees who are parents or from underrepresented minority backgrounds. Positive/surprising aspects included logistical ease of remote mentoring, the relationship-edifying result of the shared pandemic experience, mentee resilience and gratitude, and increased enjoyment of mentoring. Recommendations included practical tips, encouragement for patience and persistence, and prioritizing supporting mentees' and one's own mental well-being. Findings revealed gaps in HIV mentors' competencies, including the effective use of remote mentoring tools, how to work with mentees in times of distress, and the prioritization of mentor well-being. Mentors are in a unique position to identify and potentially address factors that may lead to mentees leaving their fields, especially parents and those from underrepresented backgrounds. We discuss implications beyond the COVID-19 pandemic.